PENGARUH MARKETING MIX TERHADAP COSTUMER LOYALTY DALAM MENGGUNAKAN MEETING PACKAGE DI SARI ATER HOTEL & RESORT - Gema Maulida, Ratna; Sukmadi, Sukmadi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This research was conducted to know Marketing Mix, Costumer loyalty, and the eefect of marketing mix on customer loyalty in sari ater & Hotel Resort. The type of research is quantitive research approach, while the level of empirical research is associate research. The data derived from questionneraire were processed using SPSS software 20.0, producing values of promotion at 70.01%, location 71,28%, Price 77.0% of 1001 and the marketing mix is still less that means customer loyalty is lower 69,72% of 1269for total score which is lower, The result of multiple regression analysys using t test and F test showed that the marketing Mix have rather strong effect on the costumer Loyalty in Sari ATer & Hotel Resort. The coefficient of determination is obtained some 93,2%, while the rest 6,8% is another factors beyond the research, for example, the quality of service